DEVELOPMENT AND PRACTICAL APPLICATION OF AN ORIGINAL METHOD OF MONITORING THE PATENCY OF THE SPINAL SPACES DURING THE REMOVAL OF LUMBOSACRAL LIPOMA - A.A. SUFIANOV; I.S. SHELYAGIN; M.R. GIZATULLIN; A.A. SUFIANOV (Avicenna Tajik State Medical University, 2021)
Objective: To assess the effectiveness of reconstructive plasty of the dura mater in patients with lumbosacral lipomas (LSL) using an original method for controlling the patency of the spinal spaces. Methods: The results of examination and treatment of 34 patients with LSL, who were operated on under the control of intraoperative ultrasonography, were analyzed. Before and after reconstructive plasty of the spinal cord and dura mater (DM), the patients underwent measurements of the anterior sagittal, posterior sagittal, common sagittal and common frontal spaces. The control group was represented by 34 patients with craniosynostosis, in whom the pathology of the spine and spinal cord was excluded, and the measurements of the above spinal spaces were taken as the anatomical norm. Results: Statistically significant differences were revealed between the value of the posterior sagittal space before opening the DM and this indicator under conditions of anatomical norm (p<0.001). No statistically significant differences between this parameter and the anatomical norm were found after reconstruction (p=0.1). The total sagittal and total frontal spaces before opening the DM did not have a statistically significant correlation with the patient's age (r=0.222, p=0.7 and r=0.214, p=0.82, respectively), while the same values after reconstructive surgery had a significant correlation with the patient's age (r=0.327, p=0.007 and r=0.392, p=0.001, respectively). Conclusion: The data obtained using the original method for monitoring the patency of the spinal spaces indicate a high efficiency of reconstructive plasty of the spinal cord and dura mater for lumbosacral lipomas, which is confirmed by statistical calculations.